Analisis Yuridis Pertanggungjawaban Pidana Pelaku Pelecehan Seksual Yang Menderita Fetishistic Disorderv (STUDI PUTUSAN NOMOR 2286/Pid.Sus/2020/PN Sby) - Kade Richa Mulyawati; Putu Ayu Candradiva Saraswati; Anak Agung Sagung Laksmi Dewi (Jurnal Preferensi Hukum, 2025)
One form of behavioral deviation that has occurred in human life is fetishistic disorder. The formulation of the problem in this study are: How is the legal regulation of the perpetrators of sexual harassment in Indonesia? and How is the form of criminal liability for perpetrators of sexual harassment who suffer from fetishistic disorder case study of decision Number 2286/Pid.Sus/2020/PN Sby. This research uses a normative methodological approach that focuses on legal analysis and legislation, and utilizes a conceptual approach. The result of this research is that fetish behavior can only be classified as obscene acts if there are acts of coercion, kissing, or sexual touching of the victim and this can fulfill the elements of the article on violation of decency in the Criminal Code. The perpetrator was sentenced to imprisonment and a fine for disseminating personally intimidating electronic information. The government should immediately harmonize the laws and regulations governing the term sexual harassment in the Criminal Code in detail. This is very necessary in imposing appropriate criminal sanctions on the perpetrator.